483 Child restraint seat law in Malaysia 2019: post-policy commitment begins - Mani, Kulanthayan KC; Ahmad, Norliza; Mansor, Zawiah; Sambasivam, Sivasankar (BMJ Publishing Group, 2024)
Background In 2022, Malaysia records road crashes every 60 seconds and fatalities every 90 minutes. Car passengers take up close to 18% of total road fatalities and need to be restrained to prevent injuries. In December 2019, the government passed the new law on Child Restraints Seat (CRS). However, the implementation was deferred due to the COVID-19 pandemic and movement control order. As children resume travel in this post-pandemic phase, there is a vital need to provide a safe travel environment for them in their cars. Thus, implementing the law is not the only means to increase the usage of CRS. Self-compliance in realizing the benefit of a safety product is also a means to be explored by families, institutions, and employer organizations.